Improved Pohlig - Hellman using Sieve of Eratosthenes for Three-Pass Protocol Security Enhancement - Robbi Rahim (TEM Journal, 2021)
Password-based is widely used as an exchange model in many areas such as smartphones, computers and other devices in which the keys are directly distributed to the recipients. Therefore, the implementation of cryptographic protocols without key exchange remains an undesirable area. The three-pass protocol is an instrument that enables sender and receiver to send encrypted data without any of the keys being transmitted to recipients. Furthermore, this process eliminates key exchange between senders and recipients when there is three ways direct communication using their own key.